Fixed Points and Endpoints of Set-Valued Contractions in Cone Metric Spaces - Ing-Jer Lin; Chi-Ming Chen; Mirko Jovanović; Tzi-Huei Wu (Abstract and Applied Analysis)
The purpose of this paper is to present the fixed points and endpoints of set-valued contractions concerning with the stronger Meir-Keeler cone-type mappings in cone metric spcaes. Our results generalize the recent results of Kadelburg and Radenović, 2011; Wardowski, 2009.